Improved the Discourse Pattern in Students Argumentation Through the Use Of Scaffolding on Strategy Argument-Driven Inquiry - Neni Hasnunidah; Herawati Susilo; Mimien Henie Irawati; Hedi Sutomo (Universitas Sebelas Maret, 2015)
Research has been conducted to compare the quality of argumentation of students participating in basic biology course based the discourse patterns between Argument-Driven Inquiry (ADI) and Argument-Driven Inquiry with Scaffolding (ADIS) strategy. Data collected through argumentation observation sheets and audio-visual recording followed by transcription of course. A total of 150 students are involved as research subjects. TAP (Toulmin Argumentation Pattern) comprising components of claim, warrant, backing, and rebuttal has been used to analyze argumentation discourse. The quality of argumentation were qualitative descriptive analyzed by complexity of argumentative discourse. T-test was used to determine differences in the average level of the quality of the argumentation between ADI and ADIS class. The results showed that the quality of the students argumentation in the ADIS class better than students in the ADI class. The ability of students in ADIS class on developing more than one rebuttal that has the explicit data, warrant or backing against arguments than student in ADI class. In general, very few students are able to develop a rebuttal to the data, warrant or backing another students. Most students rebuttal submitted is not based on a explicit rebuttal by the adequate of data, warrant, or backing.Keywords: discourse pattern, argumentation, argument-driven inquiry, scaffolding